Neuroophthalmic abnormalities in supranuclear palsy (Ukrainian Journal of Ophthalmology, 2025)
Background: Progressive supranuclear palsy (PSP) is the most common atypical parkinsonism with various movement disorders and oculomotoric abnormalities.Purpose: To identify major neuroophthalmic manifestations in different clinical phenotypes of PSP.Material and Methods: The study was conducted at the Odesa regional clinical hospital in 2011 to 2021.Twenty one patients with PSP (including one patient with PSP combined with Hallervorden–Spatz disease and levodopa-induced hyperkynesis) underwent an examination. This included a classical neurological examination and comprehensive neuroophthalmic examination with high-field magnetic resonance imaging (MRI) of the brain and spine and videonystagmography testing. Mean patient age was 53.2 ± 1.1 years, and most patients were women (13 [61.9%]). Statistical analysis included frequency analysis.Results: PSP-P was the most common phenotype of PSP (52.4%), followed by PSP-PGF (9.5%), PSP-OM (9.5%), PSP-PI (9.5%), PSP-CBS (4.8%), PSP-SL (4.8%), PSP-F (4.8%) and PSP+GSD (4.8%). All patients showed changes in velocity and amplitude of vertical saccades. Diplopia was, however, observed in only 12 (57.1%) patients.Conclusion: Neurological and neuroophthalmic examination is decisive in establishing the diagnosis of progressive supranuclear palsy and selecting a treatment strategy. In the current study, PSP-P was the most common (52.4%) phenotype,  the frequency of PSP-OM variant was 9.5%.
Keywords: progressive supranuclear palsy; neuroophthalmology; diagnostic assessment; phenotype